Qndeel-e-adab (quwaid-wa-inshaa) class 5 - Syed maqsood (Asian education publisher Pakistan)
"Qandeel-e-Adab Class (Quwaid-wa-Inshaa)" is an educational resource focused on teaching the rules of grammar and composition in Urdu, aiming to enhance students' writing and language skills.